Learning programming using educational robotics - Aparicio, J. T. (2021)
Research reported in this paper fits into the generic problem of programming learning. In this context, the primary research objective of this study is to analyze if robotics facilitates programming learning. To tackle the problem, we developed a robotic kit and a small course. The robotic kit used Arduino platform and was presented in the context of this course. The course consisted of programming concepts. This course was taught to higher education students, with no previous programming knowledge. In the end, we analyzed the impact of the course. Results demonstrate that students showed interest in using robotics to learn computer programming. Results also showed the main adoption determinants of the robotic kit. Enjoyment is the most relevant to the robotic kit intention to use. However, perceived ease is the dimension that has more impact on robotic kit usage.